Approach to characterization of cyclic behavior of artificially bonded soils - António Joaquim Pereira Viana Da Fonseca (2009)
This paper presents some results from cyclic triaxial tests performed over soil-cement samples molded with typical silty sand from residual soil from granite. Several samples with different percentage of cement and void ratio were molded and cycled in distinct load amplitudes following the methodology of CEN (2004) in order to analyze the behavior of these mixtures in terms of the resilient stiffness and plastic deformation. The molding conditions concerning the percentage of cement, curing water content and void ratio, are represented by an index property that is the ratio of porosity () to the volumetric cement content (Civ), expressed as a percentage of the cement volume regarding the total volume.